Return to sports and minimum 2-year outcomes of hip arthroscopy in elite athletes with and without coexisting low back pain: a propensity-matched comparison - Jimenez, A. E.; Owens, J. S.; Monahan, P. F.; Maldonado, D. R.; Saks, B. R.; Sabetian, P. W.; Ankem, H. K.; Lall, A. C.; Domb, B. G. (The American Journal of Sports Medicine, 2021)
Background: Patient-reported outcomes (PROs) and return to sports (RTS) after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) have not been established in elite athletes with coexisting low back pain (LBP).